Assessing the long‐term effect of exposure to dispersant‐treated oil on fish health using hypoxia tolerance and temperature susceptibility as ecologically relevant biomarkers. (30th November 2018) - Mauduit, Florian; Farrell, Anthony P.; Domenici, Paolo; Lacroix, Camille; Le Floch, Stéphane; Lemaire, Philippe; Nicolas‐Kopec, Annabelle; Whittington, Mark; Le Bayon, Nicolas; Zambonino‐Infante, José‐Luis; Claireaux, Guy
Abstract: The ecological and economic importance of fish act as a brake on the development of chemical dispersants as operational instruments following oil spills. Although a valuable and consistent body of knowledge exists, its use in spill response is limited. The objective of the present study was to increase current knowledge base to facilitate the translation of published data into information of operational value. Thus we investigated the dose–response relationship between dispersant‐treated oil exposure and ecologically relevant consequences by combining laboratory and field experiments. Effects were examined over almost a year using juveniles of the slowly growing, commercially important European sea bass ( Dicentrarchus labrax ). A reliable interpretation of biomarker responses requires a complete knowledge of the factors likely to affect them. Interpopulational variability is of particular importance in environmental impact assessment because biomarker responses from a population collected in an impacted area are classically compared with those collected in a clean site. Our study revealed no effect of the exposure to dispersant‐treated oil on fish hypoxia tolerance and temperature susceptibility at 1 and 11 mo post exposure. Similarly, no effect of the exposure was observed on the ability of the fish to cope with environmental contingencies in the field, regardless of the dose tested. Thus we feel confident to suggest that a 48‐h exposure to chemically treated oil does not affect the ability of sea bass to cope with mild environmental contingencies. Finally, investigation of interpopulation variability revealed large differences in both hypoxia tolerance and temperature susceptibility among the 2 populations tested, suggesting that this variability may blur the interpretation of population comparisons as classically practiced in impact assessment. Environ Toxicol Chem 2019;38:210–221. © 2018 SETAC